Enforced disappearances, multiple motherhoods: outlines for a communicational mapping of absences - Alba Shirley Tamayo-Arango; Katherinne Arenas-López (Íconos)
This article attempts to perform a communicational mapping of enforced disappearances in Colombia. We do this by studying maternities that proliferate their meaning, feelings and pains as a consequence of the stresses and forces triggered by such happenings. These painful events are always reenacted by words, by social performances and in life itself. This article originates in an investigation performed about the social movement “Asociación Caminos de Esperanza Madres de la Candelaria”. This organization is mostly integrated by peasant women from the Antioquia Department, who have lost their beloved ones as a result of the Colombian armed conflict. We study the role of expressive collective agency in empowering a transformation of female or feminized subjects- either collective or individual-, through the accounts of five women who confronted violence before and after the enforced disappearance episode. Data was gathered through in-depth Interview and workshops. Personal conversations permeated the whole process and allowed to secure close communication with the participants. Rather than searching for answers, it was possible instead to formulate new questions about trajectories, connections, cuts, linkages and disjunctions among subjects. We were able to identify women who managed to successfully use the process as a way of further developing their subjectivity, which, in turn, led them to transform their lives and increase their autonomy and public prominence.